2015
DOI: 10.1021/acs.iecr.5b01183
|View full text |Cite
|
Sign up to set email alerts
|

High Purity Oxygen Production via BBCN Perovskite Hollow Fiber Membrane Swept by Steam

Abstract: BaBi 0.05 Co 0.8 Nb 0.15 O 3-δ (BBCN) ceramic hollow fiber membranes have been fabricated via a phase conversion and sintering technology. Oxygen permeation test was operated under steam as sweep gas and the highest oxygen permeation flux is 11.07 ml cm -2 min -1 with purity of around 99.8% at 950 o C. The stability of the membrane exposure to steam was also investigated by oxygen permeation studies and further characterization by SEM, EDX, ICP, XRD, FTIR and XPS techniques. BBCN hollow fiber membrane still ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…The advantages of this type of layered membrane will result in deposition of a homogeneous membrane on both sides of the alumina support and increase the stability. The presence of a finger-like structure inside the hollow fiber offers a porous but smooth surface with a mass transfer resistance much lower than that of normal porous ceramic tubes. It has been previously reported that the inner-coated Pd alloy membrane has superior properties compared to those of the outer-coated membrane. Therefore, it is believed that the current strategy of coating a Pd layer inside and a zeolite layer outside the alumina hollow fiber substrate will have better thermal and chemical stability.…”
Section: Introductionmentioning
confidence: 99%
“…The advantages of this type of layered membrane will result in deposition of a homogeneous membrane on both sides of the alumina support and increase the stability. The presence of a finger-like structure inside the hollow fiber offers a porous but smooth surface with a mass transfer resistance much lower than that of normal porous ceramic tubes. It has been previously reported that the inner-coated Pd alloy membrane has superior properties compared to those of the outer-coated membrane. Therefore, it is believed that the current strategy of coating a Pd layer inside and a zeolite layer outside the alumina hollow fiber substrate will have better thermal and chemical stability.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, we have successfully prepared ZnO hollow fibers with different microstructures through phase inversion/sintering techniques. Hollow fibers offered a higher surface-to-volume ratio and packing density than disk and large tubes. ,,,,,, Different hollow fibers have also been developed for gas separation and catalysis. The reduced wall thickness and the increased finger-like channels within the hollow fibers minimized the resistance during transportation. These advantages of hollow fibers make them interesting for industrial applications.…”
Section: Introductionmentioning
confidence: 99%
“…The charge carrier diffusion length of perovskite materials in present reports is typically between 100 to 1000 nm . Moreover, numerous studies have confirmed the charge carrier diffusion length of perovskites is directly related to its crystal size. The presence of large amounts of surface defect states will lead to the trapping of carriers and further recombination easily, resulting in transmission loss. , In addition, it has been demonstrated that when the single crystal size reaches the centimeter domain, the carrier diffusion length can increase to 175 μm, much higher than that of perovskite polycrystalline films . Therefore, by enhancing the size of the perovskite crystals, the carrier diffusion length can increase over 100 times, and thus can significantly improve the efficiency of the resulted devices. Numerous researches have been done to get large-sized crystals, but it is still a great challenge apply such in solar cells. ,, …”
Section: Introductionmentioning
confidence: 73%